The Evaluation of Urban Eco Drainage System in Makassar - Andi Subhan Mustari; Riswal Karamma; Evi Aprianti (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
The objective of study is to reduce surface water runoff in low-lying areas that potentially occurred flooding. The concept of environmentally friendly drainage is the right choice to be applied in reducing the potential for flooding and sediment buildup, especially in areas with small water absorption. The quantitative method used to analyze hydrological and flood discharge then evaluated canal capacity in urban area. Rainfall data and population development for 10 years are used to determine the planned discharge with a certain return period according to actual conditions. The result show that from the 4 types of primary canals, an average of 1.03 m3/sec can be obtained. while the evaluation results for the secondary channel obtained 7 channels with a reduced average inundation discharge of 1.97 m3/s. It can be said that the application of infiltration wells is quite effective to be used as an alternative solution in reducing inundation of urban area.